2008
DOI: 10.1128/jvi.00746-08
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Single-Cell Reproduction Cycle of Members of the Family Bromoviridae : Lessons from the Use of Protoplast Systems

Abstract: 2The development of single-cell protoplast systems is certainly one of the milestones in the history of plant virology, allowing for the analysis of viral molecular processes at the cellular level. The use of plant cell-based systems in the study of the Bromoviridae family of multipartite single-stranded plant RNA viruses facilitated the discovery and dissection of viral processes engaged in the single-cell reproduction cycle: replication, transcription, protein synthesis, movement, virion assembly, and RNA re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 134 publications
1
19
0
Order By: Relevance
“…Nevertheless, a strong labeling of vesicles and ER was showed in case of Brome mosaic virus (BMV), another member of the Bromoviridae family (Bamunusinghe et al 2011). Sztuba-Solińska andBujarski (2008) showed that the sites of BMV replication are ER membranes, and the vesicles differentiating from the ER membrane can be a potential site of particles accumulation. BMV creates special membrane structuresspherules in which replication occurs.…”
Section: Immunofluorescent and Immunogold Labeling Localization Of Cpmentioning
confidence: 99%
“…Nevertheless, a strong labeling of vesicles and ER was showed in case of Brome mosaic virus (BMV), another member of the Bromoviridae family (Bamunusinghe et al 2011). Sztuba-Solińska andBujarski (2008) showed that the sites of BMV replication are ER membranes, and the vesicles differentiating from the ER membrane can be a potential site of particles accumulation. BMV creates special membrane structuresspherules in which replication occurs.…”
Section: Immunofluorescent and Immunogold Labeling Localization Of Cpmentioning
confidence: 99%
“…1A) (Wierzchoslawski et al, 2006). The binding of another RDRP molecule to the near-by SGP promoter core hairpin which initiates the SG RNA4 transcription might pose an additional obstacle to the progression of the RDRP during (+) strand synthesis (Wierzchoslawski et al, 2006;Sztuba-Solińska and Bujarski, 2008).…”
Section: ) Dianthovirusesmentioning
confidence: 99%
“…Also, in Cucumber mosaic cucumovirus (CMV), which is closely related to BMV, the RNA3 component lacks the polyA tract and it does not result in formation of homologous recombinants (de Wispelaere et al, 2005). Yet another effect might be due to the close proximity of the sgRNA4 transcription site, which may enhance RdRp recruitment (Sztuba-Solińska and Bujarski, 2008).…”
Section: In Vitro Rdrp Copying: the Primer Extension Modelmentioning
confidence: 99%